2021
DOI: 10.1111/hsc.13235
|View full text |Cite
|
Sign up to set email alerts
|

Parent engagement and therapeutic alliance in allied health teletherapy programs

Abstract: Teletherapy services are being increasingly provided by allied health professionals to address major inequities of access. While clinical outcomes and stakeholder satisfaction are crucial for paediatric teletherapy's continued viability, processes for increasing parent/caregiver satisfaction, and for modifying aspects of caregiver engagement to improve outcomes, are under-researched. Studies of in-person therapy have shown that engagement, satisfaction and outcomes are influenced by the development of therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Although previous work from our institution found high levels of satisfaction among patients receiving telehealth services (Tanner et al, 2020), future research could explore the link between patient satisfaction and visit length and/or patient engagement. One study found that patient engagement and therapeutic alliance were associated with a preference for telehealth services (Fairweather et al, 2022). Another study found that ease of process in terms of administration and technology can also affect satisfaction with telehealth services (Guntu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous work from our institution found high levels of satisfaction among patients receiving telehealth services (Tanner et al, 2020), future research could explore the link between patient satisfaction and visit length and/or patient engagement. One study found that patient engagement and therapeutic alliance were associated with a preference for telehealth services (Fairweather et al, 2022). Another study found that ease of process in terms of administration and technology can also affect satisfaction with telehealth services (Guntu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Through the frequent use of affective touch as a mode of communication, it can help to develop behavioral synchrony, coupling, and a shared dynamic neural code between the practitioner, patient and their family (95). This can lead to an increase in rapport, trust, and mutual respect in the therapeutic relationship, allowing the caregiver to provide more supportive and autonomous care to the child's clinical needs (96,97). Furthermore, incorporating family-centered care, which takes into consideration the values, attitudes, and context of the child's family in conjunction with the biomedical aspects of treatment, is regarded as best practice in pediatrics.…”
Section: The Impact Of Touch On Biobehavioural Synchrony and Infant P...mentioning
confidence: 99%
“…Furthermore, incorporating family-centered care, which takes into consideration the values, attitudes, and context of the child's family in conjunction with the biomedical aspects of treatment, is regarded as best practice in pediatrics. The use of therapeutic affective touch in conjunction with family-centered care can help to attain patient satisfaction, biobehavioral synchrony, therapeutic alliance, and cooperative communication and improve both physical and psychological well-being for conditions such as juvenile idiopathic arthritis (96)(97)(98)(99)(100).…”
Section: The Impact Of Touch On Biobehavioural Synchrony and Infant P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Telerehabilitation is defined as therapy occurring remotely over a telecommunication platform such as telephone or video conferencing ( 9 ). Increasingly, telerehabilitation services are being provided by allied health clinicians and are proposed as a solution to barriers encountered when accessing in-person rehabilitation services, such as the time and cost associated with travelling to appointments ( 7 , 10 ). In a 2023 systematic review examining the effectiveness of telerehabilitation in children with developmental disabilities, telerehabilitation was found to be more effective when compared to no treatment for outcomes such as functional performance, hand function, visual perception, and behaviour or as effective when compared to no treatment (i.e., waitlist) and usual treatment, respectively ( 11 ).…”
Section: Introductionmentioning
confidence: 99%